Sheet music in the Philippines a preliminary study - Montes, Teresa A.; Prudente, Felicidad (College of Music, University of the Philippines, 2003)
This paper is a preliminary study on sheet music produced in the Philippines. It aims to trace and describe the history of music printing and publishing in the country through sheet music. Sheet music by its physical description are "single sheets printed on one or both sides, folios wherein one sheet is folded in half to form four pages, folios with loose half-sheet inserted to make six pages, double-folios (an inner folio inserted within the fold of an outer folio to make eight pages) and double-folios with loose half-sheet inserted within the fold of an inner folio to produce ten pages.
Thesis (B. M. Musicology) -- University of the Philippines Diliman.
Includes bibliography and index.
Keywords: Music -- Philippines -- Publishing